(3aj GdEbJUGO GdSjGSj (B:s (3GdfbhO hGdfXe GdfbOjI (B/s - (3YWhj, ahRjs ((3HjQhJ(B: s (3OGQ GdacQ GdYQHj(B, s, 1989)
(3GdJjGQGJ GdGbJUGOjI GdMOjKI,fTCI GdfbhO hJWhQgG,WHjYI GdfbhO,GdfXe GdfbOjI,GdGUOGQ GdfbOjs
(3HHdjhZQGajG(B:301-307s
Keywords: (3GdGbJUGOs; (3GdfbhOs